Familias disfuncionales y los efectos psicológicos en los adolescentes del décimo año de la Unidad Educativa 23 de Junio, Cantón Baba, Provincia los Ríos - Vásquez Torres, Samara Neferti (2017)
The present project used field and documentary research, with its types, methods and techniques therefore through what was used many of the negative situations that caused being part of a dysfunctional family, data that were obtained from students, parents Of family and teachers of the Tenth year of the Educational Unit 23 of June, Baba county, Province Los Ríos. The aim is to reduce the psychological effects on adolescents because of the families, in this work the importance of the family and the strengthening of their affective bonds are exposed, the problems faced by the adolescents who are members of these families are exposed. Analyze the different aspects that surround the adolescents in their different contexts. With this research carried out, the aim is to create awareness in families, to be more integrated, more functional to avoid future problems, and for each family to contribute to social welfare from their own family welfare. For this reason, a proposal was created to help achieve the objectives and improve the lifestyle of adolescents and their families.